The FLASH project: improving the tools for flash flood monitoring and prediction across the United States - Gourley, Jonathan J.; Flamig, Zachary L.; Vergara, Humberto; Kirstetter, Pierre-Emmanuel; Clark, Robert A.; Argyle, Elizabeth; Arthur, Ami; Martinaitis, Steven; Terti, Galateia; Erlingis, Jessica M.; Hong, Yang; Howard, Kenneth W. (American Meteorological Society, 2017)
This study introduces the Flooded Locations and Simulated Hydrographs (FLASH) project. FLASH is the first system to generate a suite of hydrometeorological products at flash flood scale in real-time across the conterminous United States, including rainfall average recurrence intervals, ratios of rainfall to flash flood guidance, and distributed hydrologic model–based discharge forecasts. The key aspects of the system are 1) precipitation forcing from the National Severe Storms Laboratory (NSSL)’s Multi-Radar Multi-Sensor (MRMS) system, 2) a computationally efficient distributed hydrologic modeling framework with sufficient representation of physical processes for flood prediction, 3) capability to provide forecasts at all grid points covered by radars without the requirement of model calibration, and 4) an open-access development platform, product display, and verification system for testing new ideas in a real-time demonstration environment and for fostering collaborations.